Теоретичні підходи до визначення принципів та методів планування діяльності підприємства - Говорушко, Тамара Андріївна; Приходько, Леся Олександрівна (My University, 2012)
У статті досліджено сутність поняття «планування», його характеристики та значення. Розкрито та систематизовано основні принципи планування та методи, що використовуються для їх виконання в процесі планування діяльності підприємства.

The essence of planning consists in development and substantiation of the purposes, definition of the best methods and ways of their achievement with the effective use of all kinds of resources necessary for performance of desired tasks in establishment of their interaction. In planning the substantiation of taken decisions and the forecast of expected results are based on theoretical conditions and principles and also on practical data and facts. There is no common opinion on classification, grouping and determining of principles and methods of planning. The article features and systematizes the main principles of planning, development of their forming. A. Fayol was the first to formulate the general principles of planning, later they were complemented by R. Akoff. The article also describes the methods which are used for performance of these principles during planning activity of the enterprise. The process of planning is an important part of enterprise governance, has a positive effect on increase in profitability, introduction of high organizational culture and creates a basis for provision of efficient control of the enterprise.
Keywords: методи планування; планування; управління; функції управління; принципи планування; methods of planning; plan; planning; management; functions of management; principles of planning; кафедра фінансів